Vulnerabilities and life stressors of people presented to emergency departments with deliberate self-harm; consolidating the experiences to develop a continuum of care using a mixed-method framework - Devassy, Saju Madavanakadu; Scaria, Lorane; Varghese, Jaicob; Benny, Anuja Maria; Hill, Nicole; Joubert, Lynette (Frontiers in Public Health, 2023)
Objective Suicide is a crucial public health concern. However, the interactions between bio psychosocial vulnerabilities and stressors leading to deliberate self-harm behavior remain unexplored, especially in the Indian context. This study examined the experiences leading to self-harm behavior among people who presented to emergency departments with suicidal attempts. Methods In this mixed-methods study, we enrolled 44 patients who presented with self-harm behavior at three tertiary health care facilities between October and December 2019. To collect quantitative data, we employed standardized tools: General Health Questionnaire (GHQ-28), General Help-Seeking Questionnaire, Mini International Neuropsychiatric Interview, and the Brief Resilience Scale. Further, we conducted semi-structured interviews to qualitatively explore participants' life experiences and other risk factors. Qualitative analyses were performed using thematic analysis and quantitative descriptive and inferential statistics were performed using STATA software. Results The mean age of subjects were 29.8 years. The mean suicidality score for the patients was 26 (±8.7). In univariate analysis, depression and anxiety were positively associated with suicidality. While help-seeking behavior and resilience were negatively associated with suicidality. Qualitative results were centered on three major themes; life stressors, family related stressors, and social support-related vulnerabilities. The subjects' lived experiences were introduced in the backdrop of the interplay of vulnerabilities and stressors. Conclusion The biopsychosocial vulnerabilities remain dormant until it is activated by life stressors resulting in severe self-harm behaviors. Mental health team-driven assertive engagement, positive coping, and social support interventions would help prevent reattempts in people with self-harm behaviors.